2015
DOI: 10.1155/2015/192094
|View full text |Cite
|
Sign up to set email alerts
|

Geographic-Related Differences of Pituitary Adenomas Hormone Profile: Analysis of Two Groups Coming from Southeastern and Eastern Europe

Abstract: We compared the immunoprofile of pituitary adenomas from Romania and Moldova. One hundred and eighty cases coming from Romania (94 cases, group 1) and Moldova (86 cases, group 2) were assessed by immunohistochemistry regarding all six basic hormones expressed in pituitary adenomas. Specific differences and similarities were found and stated for both groups. In group 1, 70% of cases were pituitary adenomas positive for one hormone, 13% were plurihormonal, while 17% were negative. In group 2, 50,3% of the cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The possibility that Caucasian patients are predisposed to particular subtypes of pituitary tumors may also explain their increased likelihood of requiring and thus receiving surgery, for example, for non-prolactinomas, or more rapidly-growing tumors that cause visual or endocrinological abnormalities [ 15 ]. There has been relatively little investigation thus far on the extent to which pituitary hormonal characteristics vary according to geography and race; however, a study by Cimpean et al found significantly different immunohistochemical and hormonal profiles in patients with pituitary adenomas in two separate European countries [ 23 ]. Their results may lend support to the concept of specific epidemiological factors affecting the biological characteristics of pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that Caucasian patients are predisposed to particular subtypes of pituitary tumors may also explain their increased likelihood of requiring and thus receiving surgery, for example, for non-prolactinomas, or more rapidly-growing tumors that cause visual or endocrinological abnormalities [ 15 ]. There has been relatively little investigation thus far on the extent to which pituitary hormonal characteristics vary according to geography and race; however, a study by Cimpean et al found significantly different immunohistochemical and hormonal profiles in patients with pituitary adenomas in two separate European countries [ 23 ]. Their results may lend support to the concept of specific epidemiological factors affecting the biological characteristics of pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%